(untitled) (International journal of artificial intelligence, 2024)
In the evolving landscape of education, active learning and problem-based learning (PBL) have gained significant traction as transformative pedagogical methods. This paper explores the effectiveness of these approaches in various educational settings, emphasizing their role in fostering student engagement, critical thinking, and problem-solving skills. By integrating these methodologies, educators can better address the diverse needs of learners, promoting both academic achievement and personal growth.